A Multinational Cluster Randomised Controlled Trial to Assess the Efficacy of '11+ Kids': A Warm-Up Programme to Prevent Injuries in Children's Football - Rössler, Roland; Junge, Astrid; Bizzini, Mario; Verhagen, Evert; Chomiak, Jiri; Aus der Fünten, Karen; Meyer, Tim; Dvorak, Jiri; Lichtenstein, Eric; Beaudouin, Florian; Faude, Oliver (Sports medicine (Auckland, N.Z.), 2018)
OBJECTIVE: The objective of this study was to assess the efficacy of a newly developed warm-up programme ('11+ Kids') regarding its potential to reduce injuries in children's football. METHODS: Children's football teams (under 9 years, under 11 years, and under 13 years age groups) from Switzerland, Germany, the Czech Republic and the Netherlands were invited. Clubs were randomised to an intervention group and a control group, and followed for one season. The intervention group replaced their usual warm-up by '11+ Kids', while the control group warmed up as usual. The primary outcome was the overall risk of football-related injuries. Secondary outcomes were the risks of severe and lower extremity injuries. We calculated hazard ratios using extended Cox models, and performed a compliance analysis. RESULTS: In total, 292,749 h of football exposure of 3895 players were recorded. The mean age of players was 10.8 (standard deviation 1.4) years. During the study period, 374 (intervention group = 139; control group = 235) injuries occurred. The overall injury rate in the intervention group was reduced by 48% compared with the control group (hazard ratio 0.52; 95% confidence interval 0.32-0.86). Severe (74% reduction, hazard ratio 0.26; 95% confidence interval 0.10-0.64) and lower extremity injuries (55% reduction, hazard ratio 0.45; 95% confidence interval 0.24-0.84) were also reduced. Injury incidence decreased with increasing compliance. CONCLUSION: '11+ Kids' is efficacious in reducing injuries in children's football. We observed considerable effects for overall, severe and lower extremity injuries. The programme should be performed at least once per week to profit from an injury preventive effect. However, two sessions per week can be recommended to further increase the protective benefit. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02222025.
Keywords: Child; fotbal; Athletic Injuries; Football; Warm-Up Exercise; tělesná výkonnost; poranění dolní končetiny; Humans; sportovní úrazy; Leg Injuries; lidé; zahřívací cvičení; Physical Fitness; americký fotbal; Soccer; dítě